Realistik Matematika: Penerapan dalam Literasi Matematis di Sekolah Menengah Pertama (SMP) - Darmastuti, Lintang; Rahayu, Wardani; Meiliasari, Meiliasari (PAKAR Pendidikan, 2025)
The background of this research is the lack of individuals applying their mathematical theoretical knowledge into practice (real situations). The characteristics of a realistic mathematics approach with mathematical literacy skills have the sama relationship and goal, namely that an individual needs to be able to apply their mathematical knowledge to solve problems in everyday life by using and interpreting mathematics in various contexts. The aim of this reseach is to analyze the application of a realistic mathematics learning approach so that students’ mathematical literacy skill, especially at the secondary school level, can improve. This research is a systematic literature review research by searching for article material in the google scholar database indexed by Sinta, Scopus, or originating from proceedings for the results and discussion sections, with problems limited to secondary schools. The result show that by implementing a realistic mathematics education approach mathematical literacy skills can be increased. Meanwhile, during the realistic mathematics education learning process, teacher can choose learning models and learning media by paying attention to the characteristics of RME. Keywords: mathematical literacy, realistic mathematics, human activity, junior high school.